Tourism Entrepreneurship: Empirical Analysis in a Super-Priority Destination in Indonesia - Santi Agustina Manalu; Togar Mangihut Simatupang; Santi Novani (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This article explores the portrait of tourism entrepreneurship in the context of a super-priority destination. This study employed a mixed-methods approach, combining a survey of 73 tourism entrepreneurs and an in-depth interview with four entrepreneurs representing the dominant business sectors of food and beverage service, creative business, accommodation, and tourist attraction within the destination. The findings revealed that most businesses were relevant to food and beverage and creative initiatives. They were relatively mature in the tourism business, with the primary motive for the business opportunity being financial benefits. The critical business challenges identified were inadequate marketing prowess, reduction in demand, shortage of human skills and lack of collaboration among stakeholders. In general, the current development of tourism entrepreneurship in this area is in a phase of slight increase. The findings contributed to the enrichment of the literature on tourism entrepreneurship. This study also supported business development, informed policymakers, and promoted sustainable tourism development.